2010
DOI: 10.1002/jez.645
|View full text |Cite
|
Sign up to set email alerts
|

Fast and furious: effects of body size on strike performance in an arboreal viperTrimeresurus(Cryptelytrops)albolabris

Abstract: Body size has a pervasive effect on animal functioning and life history with size dependent changes in performance and physiology throughout ontogeny being common in many ectothermic vertebrates. However, as selection on juvenile life history stages is strong, juveniles often offset the disadvantages of small body size by disproportionate levels of performance. Here, we investigate size-related changes in defensive strike performance in an arboreal pit viper, Trimerusurus (Cryptelytrops) albolabris. Our data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 30 publications
2
63
2
Order By: Relevance
“…¼ 348 + 71 g, snout -vent length ¼ 91 + 5.6 cm), 6 western cottonmouth vipers (Agkistrodon piscivorus; 273 + 15.8 g, 68 + 2.4 cm), 12 western diamond-backed rattlesnakes (Crotalus atrox; 634 + 38 g, 95 + 2.0 cm) and previously published studies [2,4,10,11]. We discuss the accelerations of snake strikes in relation to the known physiological effects experienced during high accelerations, and we compare strike durations with mammalian startle-response times.…”
Section: Introductionmentioning
confidence: 74%
“…¼ 348 + 71 g, snout -vent length ¼ 91 + 5.6 cm), 6 western cottonmouth vipers (Agkistrodon piscivorus; 273 + 15.8 g, 68 + 2.4 cm), 12 western diamond-backed rattlesnakes (Crotalus atrox; 634 + 38 g, 95 + 2.0 cm) and previously published studies [2,4,10,11]. We discuss the accelerations of snake strikes in relation to the known physiological effects experienced during high accelerations, and we compare strike durations with mammalian startle-response times.…”
Section: Introductionmentioning
confidence: 74%
“…In terrestrial tetrapods, although fewer data are available, locomotor-feeding integration has been demonstrated in snakes (e.g. Frazzetta, 1966;Janoo and Gasc, 1992;Kardong and Bels, 1998;Cundall and Deufel, 1999;Alfaro, 2003;Young, 2010;Herrel et al, 2011) and lizards (Montuelle et al, 2009a;Montuelle et al, 2012). Interestingly, in one omnivorous lizard, Gerrhosaurus major, both feeding and locomotor movements are observed to be flexible in response to prey size and mobility (Montuelle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We chose our overall sample sizes based on available specimens and previously published work for both morphological (Jayne and Riley, 2007;Herrel et al, 2011) and performance investigations (Moon and Mehta, 2007;Penning et al, 2015;Penning and Dartez, 2016). For each experiment below, we provide the sample size for that specific experiment.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the muscle CSA of five epaxial muscles (semispinalis-spinalis complex, multifidis, longissimus dorsi and iliocostalis; Fig. 1) in each section of the body (following Jayne and Riley, 2007;Herrel et al, 2011) using ImageJ software (NIH; https:// imagej.nih.gov/ij/) (following Herrel et al, 2011). We chose this method of measuring muscle CSA to follow previous methods (Lourdais et al, 2005;Jayne and Riley, 2007;Herrel et al, 2011) and because a simple measure of external body width (a dimension of length) would represent only half of the possible variation in muscle cross-sectional area (length 2 ); furthermore, previous work has shown that although linear measures are significantly related to muscle crosssectional areas, they miss a considerable portion of the variation in muscle cross-sectional area (Lourdais et al, 2005, found that R 2 =0.73 for this relationship).…”
Section: Morphology and Scalingmentioning
confidence: 99%
See 1 more Smart Citation